The organic Rankine cycle: A promising technology for electricity generation and thermal pollution mitigation - Escalante, Edwin Santiago Rios [UNESP]; Balestieri, José Antônio Perrella [UNESP]; de Carvalho, João Andrade [UNESP] (Elsevier, 2022)
Waste heat emissions derived from cooling systems of the thermal power plant often discharged into rivers, lakes and seas, have been the direct cause of environmental problems for marine life. To control these wastewater discharges into the receptor water body, government regulations have been created to act as limiting factors for additional power generation from these plants. The problem can be solved with an organic Rankine cycle (ORC), which is considered a promising technology in electricity generation and an alternative to avoid the thermal pollution of aquatic ecosystems. The present work analyzes the use of an ORC system aiming to increase the thermal and overall efficiency of conventional operating systems without causing an additional thermal impact on marine species. This evaluation was based on the first and second laws of thermodynamics, applied to seven organic fluids (toluene, methanol, benzene, R11, R12, R113, R134a) and equations that linked the overall efficiency of the power plant with parameters of life quality in the rivers. Results showed that among the chosen organic fluids benzene produced the highest thermal efficiency for the ORC. Besides, an application of the proposed modelling in a thermal power plant localized near to Tubarão river, SC – Brazil was presented. Results showed that by using R113 as working fluid, it is possible to generate up to 1365.02 kWelec of additional electrical energy and increase both thermal and overall efficiency of a thermal power plant by up to 22.34% and 11.01%, respectively, without causing a thermal impact on the aquatic ecosystem. The best energy use was achieved by the recuperative ORC configuration. The Dissolved Oxygen Concentration (DOC) was reduced to 6.14 %day−1, which is consistent with the regulation of the Brazilian government regarding effluent discharges in lagoons, rivers and seas. On the other hand, considering the electricity cost at 0.16 US$kWh−1 and 5% as an annual percentage rate (APR), results in a payback period of approximately 5.3 years. Thus, the specific investment cost (SIC) of this technology was estimated at 1314.57 US$kWe−1.
Keywords: Aquatic ecosystem; Organic fluids; Organic Rankine cycle; Thermal pollution; Thermal power plant; Waste heat